The Concept and Content of the Tenth Cause Methodology of Four Aplications in Decimals Fraction - Tashpulotova Dilfuza Burxonovna (Research Parks Publishers, 2021)
The article describes the teaching methods and theories that can be used to increase the effectiveness of education in secondary schools, to teach decimals.